2019
DOI: 10.1002/sia.6659
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of a depleted uranium‐5 wt% molybdenum (U‐5Mo) alloy in UHV by AES and XPS

Abstract: Early stage oxidation of a dilute‐depleted uranium‐molybdenum alloy was analysed in situ under ultra‐high vacuum conditions by AES and XPS. At the equivalent of less than 300 ns at 1‐atm O2, U‐5Mo oxidizes to form stoichiometric UO2. No molybdenum oxidation is observed. After an oxygen dose of approximately 39 L, the oxide layer approached a limiting thickness of approximately 2.4 nm. The oxidation kinetics followed a logarithmic rate law, with the best fit to the experimental data for the oxide thickness, d, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
(78 reference statements)
0
4
0
Order By: Relevance
“…It is of interest to contrast how reactive plutonium is compared with other actinide metals. Bacon et al have reported the oxidation of a uranium molybdenum alloy, U 0.95 Mo 0.05 , in the UHV environment of the XPS spectrometer and showed that it follows a logarithmic growth rate 64 . The intensity of the oxide and metal components of U4f region was extracted by curve fitting, and the oxide thickness was calculated as a function of time assuming a uniform film.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is of interest to contrast how reactive plutonium is compared with other actinide metals. Bacon et al have reported the oxidation of a uranium molybdenum alloy, U 0.95 Mo 0.05 , in the UHV environment of the XPS spectrometer and showed that it follows a logarithmic growth rate 64 . The intensity of the oxide and metal components of U4f region was extracted by curve fitting, and the oxide thickness was calculated as a function of time assuming a uniform film.…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of the in situ oxidation in UHV of α‐Pu (blue), δ‐Pu(Ga) (red) and logarithmic growth under similar conditions of a U–Mo alloy (black line) 64 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations